KERAGAMAN DAN LAYANAN EKOLOGI MAKROFAUNA EPIGEIK PADA PERTANAMAN WORTEL (Daucus carota L.) YANG DIBERI BERBAGAI IMBANGAN PUPUK ORGANIK DAN ANORGANIK - Widyatmani Sih Dewi; Putri Handayani; Sumani Sumani (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2008)
Title : Diversity and Ecological Services of Epigeic Macrofauna in Carrot Crop (Daucus carota L.) with Some Proportions of Organic and Inorganic Fertilizers. Recently ecological services by macrofauna diversity to sustainable production function of agroecosystem got a lot of attention. Epigeic macrofauna is diverse of macrofaunas which their life and activities are on the land surface, act as decomposer, litter transformer, and`predator, so they are important to keep ecosystem stability. Inorganic fertilizer usage continually on carrot crop without organic fertilizer can reduce soil macrofauna diversity. Improvement can be done by the use of organic and inorganic fertilizer equally. The aim of this research was to measure epigeic macrofauna diversity and their ecological services to carrot production by giving some proportions of organic and anorganic fertilizer. The research conducted in the end of December 2007 in a farmer field in Tawangmangu. It use RAKL (Random Completly Block Design) with single factor treatment. The treatment was fertilizer type usage proportion of organic and inorganic fertilizer. They were composed of 9 proporsition composition as follows: control, 50% inorganic fertilizer, 100% inorganic fertilizer, 50% organic fertilizer, 50% organic fertilizer added by 50% inorganic fertilizer, 50% organic fertilizer added by 100% inorganic fertilizer, 100% organic fertilizer, 100% organic fertilizer added by 50% inorganic fertilizer, 100% organic fertilizer added by 100% inorganic fertilizer. 100% inorganic fertilizer were composed of Urea 150 kg ha-1, SP 36 200 kg ha-1, and KCL 100 kg ha-1. 100% dosage organic fertilizer was 20 tons ha-1. To recognize the treatment effect is done by F test and close relationship among variables tested by corelation analysis. The result showed that organic and inorganic fertilizer proportion didn’t significant to diversity, population dencity and biomass epigeic macrofauna, but affected to β caroten content of carrot. Hymenoptera was dominant macrofauna in carrot crop. Macrofauna function to increase β caroten of carrot is indirect. Key words: fertilizer proportion, epigeic macrofauna,  caroten, Hymenoptera, ecological service